If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 = -5x + 6 Reorder the terms: -6 = 6 + -5x Solving -6 = 6 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -6 + 5x = 6 + -5x + 5x Combine like terms: -5x + 5x = 0 -6 + 5x = 6 + 0 -6 + 5x = 6 Add '6' to each side of the equation. -6 + 6 + 5x = 6 + 6 Combine like terms: -6 + 6 = 0 0 + 5x = 6 + 6 5x = 6 + 6 Combine like terms: 6 + 6 = 12 5x = 12 Divide each side by '5'. x = 2.4 Simplifying x = 2.4
| 9-2+5=260 | | 0.5(x+4)-(10x+9)=-65 | | -.5=4-4.5x | | 4x+(-3)=1 | | 11q=33 | | y=0.80(55)+136 | | 4x+(-3)=2 | | 8x-2=-9+7y | | .3(3x+6)=8x+10 | | 5(6+3x)=105 | | -5y+6=y+9 | | (-9-12)x=8-4x | | y=0.80(45)+136 | | 5x+-2x+5x=8 | | 20/(-4)=c | | x^2+x+30=0 | | .75x-1.25=-2 | | 64y^3-2=y-128y^2 | | 3h-15+h=5.2 | | y=0.80(35)+136 | | 3x-6=8(x-9) | | -10+3x=-2x+45 | | 8x-2=9+7y | | .20x+x=60 | | 3(x-1)-2=1/2(4x-8) | | (x+11)+(x+19)=16 | | y^2-36y-64=0 | | .6x+6.6=3.3 | | y^2-36y+64=0 | | m^3-121m=0 | | y=-0.80(25)+136 | | 14+2k-22=k |